Analisis Dampak Penggunaan Alat Peraga pada Pembelajaran Matematika di SD - Dhea Nanda Lazuarni; Yurika Wihelmina; Josep Nainggolan; Maya Alemina Ketaren; Elvi Mailani (Lembag, 2024)
This research aims to understand in depth about mathematics and how teaching aids in learning, especially in mathematics subjects, help students understand abstract mathematical concepts. The literature study method (qualitative approach) in this research was also used for the ability to obtain information from various sources related to mathematics learning theory, the benefits of using teaching aids, and so on. This research also briefly explains how behaviorism, cognitivism and constructivism can enable students to build their understanding by increasing motivation by teachers and ensuring that the teaching aids used are effective both over time and in the learning process.